Teichoic Acid Polymers Affect Expression and Localization of dl-Endopeptidase LytE Required for Lateral Cell Wall Hydrolysis in Bacillus subtilis - Kasahara, Jun (J Bacteriol, 2016)
In Bacillus subtilis, the dl-endopeptidase LytE is responsible for lateral peptidoglycan hydrolysis during cell elongation. We found that σ(I)-dependent transcription of lytE is considerably enhanced in a strain with a mutation in ltaS, which encodes a major lipoteichoic acid (LTA) synthase. Similar enhancements were observed in mutants that affect the glycolipid anchor and wall teichoic acid (WTA) synthetic pathways. Immunofluorescence microscopy revealed that the LytE foci were considerably increased in these mutants. The localization patterns of LytE on the sidewalls appeared to be helix-like in LTA-defective or WTA-reduced cells and evenly distributed on WTA-depleted or -defective cell surfaces. These results strongly suggested that LTA and WTA affect both σ(I)-dependent expression and localization of LytE. Interestingly, increased LytE localization along the sidewall in the ltaS mutant largely occurred in an MreBH-independent manner. Moreover, we found that cell surface decorations with LTA and WTA are gradually reduced at increased culture temperatures and that LTA rather than WTA on the cell surface is reduced at high temperatures. In contrast, the amount of LytE on the cell surface gradually increased under heat stress conditions. Taken together, these results indicated that reductions in these anionic polymers at high temperatures might give rise to increases in SigI-dependent expression and cell surface localization of LytE at high temperatures. IMPORTANCE The bacterial cell wall is required for maintaining cell shape and bearing environmental stresses. The Gram-positive cell wall consists of mesh-like peptidoglycan and covalently linked wall teichoic acid and lipoteichoic acid polymers. It is important to determine if these anionic polymers are required for proliferation and environmental adaptation. Here, we demonstrated that these polymers affect the expression and localization of a peptidoglycan hydrolase LytE required for lateral cell wall elongation. Moreover, we found that cell surface decorations with teichoic acid polymers are substantially decreased at high temperatures and that the peptidoglycan hydrolase is consequently increased. These findings suggest that teichoic acid polymers control lateral peptidoglycan hydrolysis by LytE, and bacteria drastically change their cell wall content to adapt to their environment.